2021
DOI: 10.1038/s41380-020-00984-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of patients with a severe major depressive episode treated with electroconvulsive therapy

Abstract: Although large genome-wide association studies (GWAS) of major depressive disorder (MDD) have identified many significant loci, the SNP-based heritability remains notably low, which might be due to etiological heterogeneity in existing samples. Here, we test the utility of targeting the severe end of the MDD spectrum through genome-wide SNP genotyping of 2725 cases who received electroconvulsive therapy (ECT) for a major depressive episode (MDE) and 4035 controls. A subset of cases (n = 1796) met a narrow case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…It has previously been demonstrated that systemic administration of all- trans retinoic acid depletes serotonin by over 40% in the rat brain 94 , supporting the serotonin system as a convergent target of retinoid-regulated pathways. As GWAS of MDD begins to explore severe, treatment-refractory cases 7 , it will be interesting to see whether associated variation still shows such convergence, as treatment-resistant depression (generally, non-response to two or more classes of antidepressant) effectively signifies non-response to multiple serotonergic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that systemic administration of all- trans retinoic acid depletes serotonin by over 40% in the rat brain 94 , supporting the serotonin system as a convergent target of retinoid-regulated pathways. As GWAS of MDD begins to explore severe, treatment-refractory cases 7 , it will be interesting to see whether associated variation still shows such convergence, as treatment-resistant depression (generally, non-response to two or more classes of antidepressant) effectively signifies non-response to multiple serotonergic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Family studies have demonstrated that MDD risk is at least 30% heritable 5,6 . More recently, genome-wide association studies (GWASes) have demonstrated similar estimates for severe MDD 7 , and have helped narrow in on associated single nucleotide polymorphisms (SNPs) [8][9][10][11][12] , a tantalizing entry point for understanding the biology of MDD. However, GWAS studies do not identify causal variants, but rather implicate wider co-inherited regions consisting of many SNPs in linkage disequilibrium (LD).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the Q-ECT have been used in several studies [9,19,20]. For these studies to produce reliable and useable results, it is important that the data source is valid.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…7,10 Conversely, a recent study of the genetics of patients with major depressive disorder treated with elec troconvulsive therapy (ECT) -arguably a much more severe and more specific diagnosis -yielded SNP heritability about 4 times greater than a standard genomewide association study of major depression. 11 In addition to the core psychiatric diagnosis, other fea tures come into play. For instance, while structural brain imaging studies of bipolar disorder found reproducible dif ferences from healthy unaffected individuals, it appears that some of the findings are not due to the disorder itself, but rather are secondary to metabolic factors such as obesity or insulin resistance that are frequently comorbid with severe mental illness.…”
Section: The Moving Target Of Psychiatric Diagnosis Martin Alda MDmentioning
confidence: 99%